(untitled) (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
The declining cost of solar technology and declaration of Japan, China, and Korea to not invest in new coal power plants has opened up new possibilities for the expansion of solar deployment worldwide. Bangladesh has also scrapped the plan to build new coal power plant like many other lower middle-income countries in Asia. However, the lower middle-income countries were not able to take the opportunity of the declining solar cost in last one decade and the growth of solar remained in the formative phase for most of the developing countries. Bangladesh has already missed the target to generate 10% from renewable by the year 2020. The increasing emphasis on solar globally and locally has pushed the government to set ambitious targets without considering the techno-economic, socio-technical, and political feasibility of solar. This research has used process tracing based on policy documents and interviews to explore the mechanisms through which solar deployment grew slowly in Bangladesh. Then, this paper found out the feasible, moderately feasible, ambitious, and highly ambitious solar targets of Bangladesh and identified the factors that can increase the multi-dimensional feasibility of solar targets. It shows that market mechanism alone cannot increase feasibility of the target and argues that socio-technical and political feasibility must also be considered in setting realistic target. Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp.33-56